Answer: g(x) = (-2/3)*x^2
============================================
Work Shown:
f(x) = x^2
g(x) = a*f(x) for some constant 'a' since g(x) is a scaled version of f(x).
The value of 'a' vertically stretches f(x) upward if a > 0
If 'a' is negative, then we have a reflection going on as shown in the diagram.
We want (x,y) = (3,-6) to be on the graph of g(x). This means g(3) = -6
If we plugged x = 3 into f(x), we get
f(x) = x^2
f(3) = 3^2
f(3) = 9
So,
g(x) = a*f(x)
g(3) = a*f(3) ... replace x with 3
g(3) = a*9 ... replace f(3) with 9 since f(3) = 9
-6 = a*9 ... replace g(3) with -6 since g(-3) = -6
9a = -6
a = -6/9
a = -2/3
Therefore, this means
g(x) = a*f(x)
g(x) = (-2/3)*f(x)
g(x) = (-2/3)*x^2